Multi-stage alteration at Nifty copper deposit resolved via accessory mineral dating and trace elements - Ribeiro, Bruno; Kirkland, Chris; Hartnady, Michael; Martin, E.L.; West, E.; Polito, P. (2023)
The sediment hosted Nifty prospect is one of the most prominent Cu deposits in the Neoproterozoic Paterson Province, which girdles the eastern margin of the Archean Pilbara Craton in Western Australia. The timing of mineralization at Nifty has proved challenging to constrain despite several attempts to date it using a range of isotopic methods, including muscovite 40Ar/39Ar (total fusion) and solution ICP-MS apatite U–Pb geochronology. The region preserves a protracted and complex geological history, with potential for several generations of fluid flow/mineralisation, which necessitates a texturally-controlled geochronology approach. Here, we report in situ apatite and monazite U–Pb isotopes complemented with trace elements from both mineralized veins and matrix of the sedimentary host-rock collected via laser ablation split stream inductively coupled plasma mass spectrometry (LASS-ICP-MS). Apatite grains from pyrite- and quartz-bearing veins are enriched in middle rare earth elements (MREE) with prominent convex-upward chondrite-normalized REE profiles. This chemical signature is similar to hydrothermal apatite from the Olympic Dam high-grade bornite Cu deposit, commonly associated with MREE-enriched, lower salinity fluids, and alkaline pH conditions capable of mobilizing Cu. Hydrothermal apatite from pyrite-bearing veins associated with euhedral, concentrically zoned pyrite yields lower intercept ages of ca 810 Ma, whereas hydrothermal apatite from quartz-pyrite veins associated with pyrite replacement microstructures have variable apparent ages. Monazite grains on the margins of pyrite-bearing veins (along micro-cracks) and monazite associated with chalcopyrite in veinlets yield a weighted mean 238U/206Pb age of ca 640 Ma. These results necessitate at least two distinct hydrothermal/fluid flow events related to the formation of the Nifty Cu deposit, with the former being temporally associated with ca 830 Ma mafic intrusions. Evidence for the latter hydrothermal event is cryptic, being highly localised at a grain scale, but is broadly coeval with ca 640 Ma granitic magmatism linked to Cu–Au mineralization elsewhere in the Paterson Orogen (e.g., Telfer & Winu deposits).